The analysis of construction companies diversification alternatives - Šaparauskas, Jonas; Vilutienė, Tatjana (Technological and Economic Development of Economy, 2005)
The authors of the paper had analyzed the variety of services, geographical markets, types of objects under implementation and other ratios of activities of seven biggest Lithuanian construction companies in order to determine the optimal level of diversification of construction products, geographical markets and the number of construction related services. The results of the research have shown that it is purposeful to diversify company's activities not only by the type of activities, but also by geographical markets and the purpose of construction production. The combinations of different types of difersification influence the level of turnover growth and the change of over ratios which reflect the efficiency of construction company. As a result the optimal variants of diversification by the type of activities, by the type of construction production and geographical markets were proposed.Article in Lithuanian.Statybos įmonių veiklos diversifikacijos alternatyvų analizėSantrauka. Siekdami nustatyti optimalų geografinių rinkų skaičių statybos įmonių veiklai, optimalią paslaugu įvairovę ir optimalų diversifikacijos laipsnį, autoriai išanalizavo septynių Lietuvos stambiausių pagal veiklos rezultatus statybos įmonių veiklos rodiklius, jų statomų objektų tipus, paslaugų nomenklatūrą ir geografines rinkas. Tyrimas atskleidė, jog tikslinga diversifikuoti veiklą ne tik pagal veiklos rūšį, bet ir pagal geografines rinkas bei objektų paskirtį. Be to, nustatyta, kad įvairių tipų diversifikacijų kombinacija turi įtakos įmonės apyvartos padidėjimui bei kitų rodiklių, nusakančių įmonės veiklos efektyvumą, gerinimui. Pasiūlyti optimalūs veiklos diversifikavimo pagal veiklos rūšį, statybinę produkciją ir geografinę rinką variantai.Reikšminiai žodžiai: statybos įmonės, diversifikacija, veiklos rūšys, projektų tipai, objektų paskirtis, geografinė rinka.First Published Online: 21 Oct 2010